Exchange Site for Reading and Publication of Comics Web-Based - Iksan, Muhamad; Isa Martinus, Agust; Novianti, Dian (Ann Publisher, 2024)
This study aims to create a web-based comic reading and publishing exchange to make obtaining, reading, and publishing a comic easier. As for the background of this research, in today's modern era, when getting a comic, some people still use conventional methods, so it requires more costs, limited stock, longer time, limited storage space, and more complex maintenance and production costs—extensive distribution. Creating web-based comic reading and publication exchanges is an alternative expected to make reading comics easier and faster. Comic buyers and sellers can also easily make comic transactions because they are systemized and stored safely. Testing the reading site exchange system and web-based comic publications shows that the system has achieved the expected goals. The system can identify user roles; allows the Admin to review or confirm comics and chapters as well as manage genre and user data; provides the seller with the ability to manage data on comics, chapters, and payments; gives customers access to view a list of comics, transaction history, make purchases, and read comics; and the payment system can confirm transactions made by customers.